Passive sampling for genomic surveillance of SARS-CoV-2 in wastewater resource recovery facility: Insights for pandemic preparedness - Kabir, Pervez; Plaza-Diaz, Julio; Mercier, Élisabeth; Wan, Shen; Hegazy, Nada; Wong, Chandler; Addo, Felix; Renouf, Elizabeth; Lawal, Opeyemi U.; Goodridge, Lawrence; Graber, Tyson E.; Delatolla, Robert (Water Research, 2025)
Passive sampling provides a cost-effective alternative to conventional auto-sampling and serves as a valuable approach for wastewater surveillance in resource-limited settings. However, the feasibility of passive sampling for SARS-CoV-2 wastewater genomic surveillance (WWGS) remains underexplored in wastewater resource recovery facility (WWRF). In this study, we collected influent wastewater samples using an autosampler, COSCa-ball and Torpedo passive samplers from inlet of WWRF serving the city of Ottawa, Canada. We enriched, extracted, quantified, and sequenced samples targeting SARS-CoV-2 genome using a widely used ARTIC tiled amplicon approach. Our findings show that daily SARS-CoV-2 RNA levels were similar (p > 0.05) across the sampling methods. Although similar viral RNA was captured from passive samples, we found genomic recovery of SARS-CoV-2 from passive samplers was influenced by targeted sequencing read length, with shorter (300 bp) reads resulting in lower recovery than longer (600 bp) reads. Our study confirmed near-complete recovery of SARS-CoV-2 genomes (≥ 90 %) from the autosampler, COSCa-ball, and Torpedo samplers using longer reads. Genome sequencing parameters such as the number of raw reads, trimmed reads, mapped reads, depth of coverage and % of genome coverage was identical (p > 0.05) among the sampling methods. Genomic analyses showed similar (p > 0.05) single nucleotide variant profiles (SNV) and lineage prevalence across sampling methods, and concordance with the available clinical surveillance. Overall, the findings suggest that passive sampling of wastewater is a viable, cost-effective alternative for population-scale genomic surveillance of SARS-CoV-2 and may allow for surveillance of other pathogens, supporting future pandemic preparedness efforts.
Keywords: wastewater surveillance; genome sequencing; Single Nucleotide Variants; lineage prevalence; COSCa-ballTorpedo